2022
DOI: 10.7748/ncyp.2022.e1416
|View full text |Cite
|
Sign up to set email alerts
|

Tourette’s syndrome: challenging misconceptions and improving understanding

Abstract: Tourette Syndrome (TS) is a neurodevelopmental/ neuropsychiatric tic disorder, affecting around 1% of the school-age population. Children and young people with the condition exhibit involuntary motor and vocal/ phonic tics. Only 10% of those with Tourette Syndrome have Coprolalia. Tourette Syndrome often presents with other conditions, such as Obsessive-Compulsive Disorder, Autistic Spectrum Disorder and Attention Deficit Hyperactivity Disorder. The impact of the condition on the child and young person is mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Given that participants reported difficulties with self-stigma; compassion-focused therapy (CFT) approaches which encourage self-acceptance and the development of self-worth may be helpful. It has been suggested that responding to individuals affected by TS with compassion can support them to view their condition more positively and encourage self-acceptance (Freeman-Ferguson, 2022 ). CFT approaches may also reduce the impact of external scrutiny; potentially alleviating co-occurring anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that participants reported difficulties with self-stigma; compassion-focused therapy (CFT) approaches which encourage self-acceptance and the development of self-worth may be helpful. It has been suggested that responding to individuals affected by TS with compassion can support them to view their condition more positively and encourage self-acceptance (Freeman-Ferguson, 2022 ). CFT approaches may also reduce the impact of external scrutiny; potentially alleviating co-occurring anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Family history of neuropsychiatric disorders is hardly believed to be negative as several association studies have already established the crucial relationship of parental psychopathology in patients with epilepsy, autistic spectrum disorder, attention deficit hyperkinetic disorder, and tics. [96][97][98][99][100][101][102][103][104][105][106]…”
Section: Pitfalls In Perceptionmentioning
confidence: 99%